Environmental Crisis: An exploration of the layout and architecture of Catholic Churches since Vatican II; Why and how this must change in order for a greater centrality and understanding of the Eucharist as a historic and now modern, communal activity and liturgical celebration to be achieved - Wells, Eleanor (2020)
In this thesis, I will be discussing the liturgical and physical changes made to the Catholic Church, particularly since Vatican II. I will explore how those documents released by the Vatican were not sufficient in providing enough information on how to implement these changes effectively. I will then continue to discuss the importance of creating equality through the space which is used for worship especially the concept of female priests in relation to the space and the artwork which is seen in most churches. As well as this I shall explore how such things may persuade congregations to become more open to the concept of the female priesthood as a reflection of equality which is essential for the Eucharist to be understood as best as possible, as well as encourage community involvement in the Eucharistic tradition as a shared meal. Following this I felt that it was important I spoke of modern events, notably the Coronavirus pandemic of 2020 since this would inevitably change the face of worship spaces and how they are being used for the foreseeable future! I will further discuss how church layouts can be effective by critically analysing Liverpool Cathedrals modern and alternative layout, its strengths and its weaknesses and how we may learn from them. Finally, I will present some of my own hypothetical church designs and discuss the key uses and needs for most communities using these spaces and why these hypothetical designs are more suited to modern-day worship than the common cruciform layout which we see as the norm for most communities.